PERKEMBANGAN EKONOMI SYARIAH DI INDONESIA - Santi, Mei (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2019)
The development of Sharia economics in Indonesia is also not separated from several driving factors. Simply put, the factors are grouped into external and internal factors. External factors are the cause that comes from abroad, the development of Sharia economics in other countries. This realization then ' Mewabah ' to other countries and finally reached Indonesia. While the internal factor is the fact that Indonesia is destined to be the country with the largest Muslim population in the world. This fact raises awareness in some of the scholars and economic practitioners about the need for an economy that complies with Islamic values run by Muslim communities in Indonesia.